Editing the Shape Morphing of Monocomponent Natural Polysaccharide Hydrogel Films - Hao Hu; Chao Huang; Massimiliano Galluzzi; Qiang Ye; Rui Xiao; Xuefeng Yu; Xuemin Du (Research, 2021)
Shape-morphing hydrogels can be widely used to develop artificial muscles, reconfigurable biodevices, and soft robotics. However, conventional approaches for developing shape-morphing hydrogels highly rely on composite materials or complex manufacturing techniques, which limit their practical applications. Herein, we develop an unprecedented strategy to edit the shape morphing of monocomponent natural polysaccharide hydrogel films via integrating gradient cross-linking density and geometry effect. Owing to the synergistic effect, the shape morphing of chitosan (CS) hydrogel films with gradient cross-linking density can be facilely edited by changing their geometries (length-to-width ratios or thicknesses). Therefore, helix, short-side rolling, and long-side rolling can be easily customized. Furthermore, various complex artificial 3D deformations such as artificial claw, horn, and flower can also be obtained by combining various flat CS hydrogel films with different geometries into one system, which can further demonstrate various shape transformations as triggered by pH. This work offers a simple strategy to construct a monocomponent hydrogel with geometry-directing programmable deformations, which provides universal insights into the design of shape-morphing polymers and will promote their applications in biodevices and soft robotics.